2015
DOI: 10.1371/journal.pone.0129904
|View full text |Cite
|
Sign up to set email alerts
|

Learning Environment, Preparedness and Satisfaction in Osteopathy in Europe: The PreSS Study

Abstract: Objective1) to assess the preparedness to practice and satisfaction in learning environment amongst new graduates from European osteopathic institutions; 2) to compare the results of preparedness to practice and satisfaction in learning environment between and within countries where osteopathy is regulated and where regulation is still to be achieved; 3) to identify possible correlations between learning environment and preparedness to practice.MethodOsteopathic education providers of full-time education locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
2
12
2
Order By: Relevance
“…In Australia, Subramaniam et al [12] found that osteopathy graduates felt underprepared in medico-legal procedures, risk management, paediatrics and prognosis and management of difficult patients. Differences in perceived preparedness were also reported among European osteopathic educational institutions (OEIs) [13, 14]. These findings are similar to those from research in the field of medical education [2, 3]; however, those studies could not give an insight in which area students felt underprepared and did not assess the risks for patients safety.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In Australia, Subramaniam et al [12] found that osteopathy graduates felt underprepared in medico-legal procedures, risk management, paediatrics and prognosis and management of difficult patients. Differences in perceived preparedness were also reported among European osteopathic educational institutions (OEIs) [13, 14]. These findings are similar to those from research in the field of medical education [2, 3]; however, those studies could not give an insight in which area students felt underprepared and did not assess the risks for patients safety.…”
Section: Introductionsupporting
confidence: 59%
“…In addition, studies on medical students found that curricula [18] and ethnicity [19] may have an impact on the studies’ findings. Furthermore, gender has been found to be related to the preparedness both in medical [19] and osteopathic students [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteopathy is a complementary touch-based manual medicine primarily used by different age groups of patients ( Licciardone et al, 2013 ; Cerritelli et al, 2014 , 2015b ; Pizzolorusso et al, 2014 ; Luciani et al, 2015 , 2018 ; Schwerla et al, 2015 ; Steel et al, 2017 ) and in a wide variety of clinical conditions ( Cerritelli et al, 2011 , 2015a , 2016a , 2017b ; Cicchitti et al, 2015 ; Ruffini et al, 2016 ; Franke et al, 2017 ; Lanaro et al, 2017 ). Several studies showed positive clinical effects as compared to sham, placebo, usual care or physical devices ( Pizzolorusso et al, 2011 ; Cerritelli et al, 2013 , 2015a , 2016b ; Martelli et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with undergraduate education in the health professions, there is a dearth of studies examining the learning environment and its interrelationships with other correlates within postgraduate education including psychiatry. For example, DREEM scores are inversely associated with academic achievement [6–8], and positively correlated with quality of life [9], resilience levels [9], positive attitudes toward psychiatry [10], mindfulness [11], and perceived preparedness for practice [12] in undergraduate medical students. Poor academic self-perception has also been associated with psychological distress and poor peer support [13].…”
Section: Introductionmentioning
confidence: 99%